Application of Single Identification Number on an Identity Card (E-KTP) in the Era of the Industrial Revolution 4.0 - D Kurniasih; A Feryandi; L Nurmayanti; P D Usmany (International Journal of Research and Applied Technology (INJURATECH), 2021)
This research aims to analyze the efficiency of the Single Identification Number on the identity card (e-KTP). The method used in this study was descriptive with the survey method, and to determine the efficiency of this study, we conducted questionnaires. This research results in several factors that determine the success of the Single Identification Number's success on e-KTP, including technical and economic aspects. From some of these factors, technological factors are obtained. Meanwhile, economic factors can help people to simplify administration anywhere without having to carry a different card. Moreover, it also anticipates the scarcity of blanks. Therefore, the Single Identification Number of e-KTP can be efficient in carrying out its function as a multi-purpose single identification number in a digital card (e-KTP) that makes it easier for the public. E-KTP becomes a solution for the community problem that can use as a multifunctional card, which will make it easier for the community to carry out administrative activities. Not only that, but the community is also facilitated by only doing one organizational activity